2014
DOI: 10.1371/journal.pone.0089384
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Genetic Diversity among Ocelots in the United States during the 20th Century Linked to Human Induced Population Reductions

Abstract: Ocelots (Leopardus pardalis) in the United States currently exhibit low levels of genetic diversity. One hypothesis for this observation is that habitat fragmentation, resulting from human induced changes in the landscape during the 20th century, created island populations with highly reduced gene flow and increased genetic drift and inbreeding. In an effort to investigate this, we used a portion of the mitochondrial control region and 11 autosomal microsatellite loci to examine historical levels of genetic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 71 publications
1
15
0
4
Order By: Relevance
“…A higher diversity was observed for Amazonian ocelots [41], whereas lower values were observed in the remaining ocelot populations from the United States [16][17][18]. It is noteworthy that the microsatellite loci employed in these previous studies were not identical to ours, and therefore this comparison should not be interpreted strictly.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…A higher diversity was observed for Amazonian ocelots [41], whereas lower values were observed in the remaining ocelot populations from the United States [16][17][18]. It is noteworthy that the microsatellite loci employed in these previous studies were not identical to ours, and therefore this comparison should not be interpreted strictly.…”
Section: Discussionmentioning
confidence: 64%
“…Currently, skin trade is prohibited and the main threats to this species are habitat loss and fragmentation [15]. In this context, recent analyses have indicated that the ocelots in the United States and Mexico suffer with habitat loss and population isolation, with detectable genetic depletion as a consequence [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Such extinction processes have been relevant to the conservation of endangered felids (Janečka et al. 2008, 2014; Joshi et al. 2013; Ernest et al.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing isolation and fragmentation of wildlife populations reduces genetic diversity and facilitates inbreeding, which then initiates an extinction vortex (Keller and Waller 2002;O'Grady et al 2006). Such extinction processes have been relevant to the conservation of endangered felids (Jane cka et al 2008(Jane cka et al , 2014Joshi et al 2013;Ernest et al 2014), including species such as the Iberian lynx Lynx pardinus, Eurasian lynx Lynx lynx, and Florida panther Puma concolor coryi, which have experienced severe population bottlenecks (Schmidt et al 2011;Palomares et al 2012;Casas-Marce et al 2013). These species had H O prior to reintroduction or translocation programs that varied from 0.167 for the Florida panther, (Johnson et al 2010) to 0.31 for the Iberian lynx (Palomares et al 2012;Casas-Marce et al 2013).…”
Section: Species Reintroduction As An Experimentsmentioning
confidence: 99%
“…Wild animal populations are threatened by habitat fragmentation and poaching, which can reduce both the sizes of the populations and their genetic diversity [Janecka et al, 2014;Mondol et al, 2013;Rivera-Ort ız et al, in press]. Chimpanzees are particularly vulnerable to such threats due to their slow reproduction [Nishida et al, 2003].…”
Section: Introductionmentioning
confidence: 99%